Post-school education in shrinking rural regions: experiences and solutions from Scotland and Sweden - Tent, Nathalie; Syssner, Josefina; Mose, Ingo; Rennie, Frank (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
Abstract Against the backdrop of shrinking populations, new strategies for maintaining services of general interest in European rural areas are required at both a European and a German level. With regard to this, the field of post-school education as a service of general interest is seen as playing an important role with considerable effects on regional development processes. Educational institutions, traditionally highly centralised, have been shown to influence decisions on staying in or leaving rural areas and thus can further intensify regional demographic developments. In this paper, we examine two examples of post-school educational opportunities in Scotland and Sweden that have been able to establish themselves in a rural setting affected by shrinking trends. Our interpretation is that the continued stability of these examples is due to the ability of local actors to utilise local resources in a meaningful way. The aim of this paper is therefore to contribute to a structured understanding of how local actors manage limited resources to provide services of general interest in the environment of rural, sparsely populated regions in the long term. To enable a systematised analysis of our data, we use an analytical framework originally developed to understand the resources generated by informal planning practices in rural areas.